Integrative Pediatrics: Looking Forward - Hilary McClafferty (MDPI AG, 2015)
Increase in the prevalence of disease and illness has dramatically altered the landscape of pediatrics. As a result, there is a demand for pediatricians with new skills and a sharper focus on preventative health. Patient demand and shifting pediatric illness patterns have accelerated research in the field of pediatric integrative medicine. This emerging field can be defined as healing-oriented medicine that considers the whole child, including all elements of lifestyle and family health. It is informed by evidence and carefully weighs all appropriate treatment options. This Special Issue of Children, containing a collection of articles written by expert clinicians, represents an important educational contribution to the field. The goal of the edition is to raise awareness about integrative topics with robust supporting evidence, and to identify areas where more research is needed.